PERAN TUTOR DALAM PELAKSANAAN METODE QIRO’ATI DI TPQ PAUDIT AL HASANAH - Ari Angga; Suardi Jasma; Ririn Gusti (UNIB Press, Universitas Bengkulu, 2020)
Learning the Qur'an with the Qiro'ati method is the system and how to read it smoothly, quickly, precisely, correctly, and in tartil without having to be spelled. Then the implementation model is to use props for classical implementation which contains material that is in the pages of the volume book Qiro'ati. The instructor must conduct Qiro'ati education and training so as to obtain an official diploma that can be used to teach the Qiro’ati method. Then the purpose of this research is to find out what methods are used, how the learning process is, and to find out the supporting and inhibiting factors. This research uses descriptive qualitative research methods. The research was conducted at the Al-Qur'anah Education Park PAUDIT Al Hasanah Pagar Dewa Bengkulu City on March 5 to April 5, 2019. The subjects of the study were the head and coordinator of the TPQ itself and the TPQ PAUDIT teacher Al Hasanah Pagar Dewa Bengkulu City. Keywords: Role of Tutors (Ustad / Ustadzah), Al Qur'an Learning, Qiro'ati Method